"As Luck Would Have It": Privilege, Agency, and Happenstance in the Life Stories of US American Immigrants to Costa Rica, 1960-1980. (1st September 2017) - Shragai, Atalia
Abstract: This article examines the rhetorical strategies and discursive patterns in the life stories of US Americans who immigrated to Costa Rica, chiefly during the 1960s and 1970s. Based on dozens of oral histories with these immigrants, this study analyzes the significance of the life story as a tool of identity-making and self-representation. The common narrative of coincidental migration among these immigrants was constructed in response to the growing criticism of the US Americans' presence in Costa Rica. More significantly, it testifies to the predicament of these US expats, many of whom identified with the 1960s counterculture in the US, as they negotiated their privileged status as US immigrants in Costa Rica and their own agency in contributing to economic and cultural changes in their adopted county.